PERAN TAX PLANNING DALAM MENGOPTIMALKAN PEMBAYARAN PAJAK PERTAMBAHAN NILAI TERUTANG CV.SHD - Rosalia Antika (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
This study aims to analyze the role of tax planning in optimizing the payment of Value Added Tax (VAT) at CV.SHD, a trading company registered as a Taxable Entrepreneur (PKP). The main issue faced by the company is the imbalance between output VAT and input VAT due to delays in receiving tax invoices from suppliers. This condition has led to increased VAT liabilities and frequent corrections in tax reporting. The research adopts a descriptive qualitative approach by collecting data through interviews, direct observation, and documentation of VAT transactions from January 2024 to January 2025. The analysis is conducted by comparing patterns of VAT reporting and invoice management to evaluate the effectiveness of the company’s tax planning strategy. The findings reveal that although tax planning has been implemented, it remains informal and undocumented, making it reactive and less effective. Irregularities in tax administration have disrupted VAT reporting and reduced substantive compliance. These findings highlight the importance of structured tax planning to reduce fiscal risk and promote sustainable tax compliance.